Growth Mechanism during the Early Stages of electrodeposition of Bismuth telluride films. (20th August 2015) - Zimmer, Alexandre; Broch, Laurent; Boulanger, Clotilde; Stein, Nicolas
Abstract: An optical-electrochemical study on the initial stages of bismuth telluride (Bi2 Te3 ) electrodeposition onto gold substrate is presented in this work. Numerical methods were applied on both electrochemical and optical data to obtain the relevant kinetic parameters from electrocrystallization theoretical equations and ellipsometric models in order to describe this system in the relevant 0-15 seconds range. The in-situ ellipsometry and electrodeposition analysis reveals a three-step mechanism. After an induction time including the double layer charge, the formation of a monolayer of tellurium is highlighted, followed by the adatom surface diffusion. Then, the growth of three-dimensional Bi2 Te3 crystallites is observed according a progressive nucleation and a linear growth rate. Experimental and theoretical details about each technique are given and analyzed.